Long Term Outcomes of Kidney Transplantation With Primary Glomerulonephritis. (July 2018) - Yeo, Sangmok; Park, Hayeon; Kang, Seong Sik; Park, Woo Yeong; Jin, Kyubok; Han, Seungyeup; Park, Sung Bae
Abstract : Introduction: The clinical outcomes after kidney transplantation (KT) vary according to the types of glomerulonephritis (GN) causing end-stage renal disease (ESRD). In addition, the recurrence of GN has a significant impact on the outcomes of KT. In the present study, we evaluated clinical outcomes of KT in patients with biopsy-proven GN. Methods: All KT recipients who had biopsy proven GN and had been transplanted between Nov. 1982 and Jan. 2017 were enrolled. We investigated the incidence of recurrent GN and analyzed the factors associated with recurrence, allograft survival, and patient survival. Results: Of 1253 patients who received KT, 183 had a biopsy-proven GN as the cause of ESRD. The types of GN were immunoglobulin A nephropathy (IgAN) in 95 patients, focal segmental glomerulosclerosis (FSGS) in 47, membranous proliferative glomerulonephritis (MPGN) in 14, membranous glomerulonephritis (MGN) in 9, lupus nephritis in 8, rapid progressive glomerulonephritis (RPGN) in 6, and alport syndrome in 4. The mean follow up duration was 103 ± 81.7 months. Recurrent GN occurred in 36 patients (19.7%) and recurrence rate was 25.5% in FSGS, 22.2% in MGN, 21.4% in MPGN and 20.0% in IgAN. The recurrence of GN was more common in younger patients at the time of KT (p=0.03). Twenty of the 36 patients with recurrent GN lost their allograft due to recurrence. Discussion: The rate of graft failure in recipients with recurrence was higher than those without recurrence (55.6%, 18.4%, p=0.000). The recurrence of GN rather than the type of GN was a significant risk factor for allograft loss. (adjusted hazard ratio 1.89 [1.004-3.368]). Conclusion: The recurrence of GN was significant risk factor for allograft loss. In particular, younger recipients were more likely to go through recurrence after KT. Further studies are required to evaluate optimal strategies to prevent and treat recurrent GN after KT.